Effects of swimming training on aerobic capacity and exercise induced bronchoconstriction in children with bronchial asthma. Issue 3 (1st March 1999) - Matsumoto, I; Araki, H; Tsuda, K; Odajima, H; Nishima, S; Higaki, Y; Tanaka, H; Tanaka, M; Shindo, M
Abstract : BACKGROUND: A study was undertaken to determine whether swimming training improved aerobic capacity, exercise induced bronchoconstriction (EIB), and bronchial responsiveness to inhaled histamine in children with asthma. METHODS: Eight children with mild or moderate asthma participated in swimming training every day for six weeks. The intensity of training was individually determined and set at 125% of the child's lactate threshold (LT), measured using a swimming ergometer. Another group of eight asthmatic children served as control subjects. Aerobic capacity and the degree of EIB were assessed by both cycle ergometer and swimming ergometer before and after swimming training. RESULTS: The mean (SD) aerobic capacity at LT increased by 0.26 (0.11) kp after training when assessed with the swimming ergometer and by 10.6 (4.5) W when assessed with the cycle ergometer, and these changes were significantly different from the control group. The mean (SD) maximum % fall in forced expiratory volume in one second (FEV1 ) to an exercise challenge (cycle ergometer) set at 175% of LT decreased from 38.7 (15.4)% before training to 17.9 (17.6)% after training, but with no significant difference from the control group. There was, however, no difference in histamine responsiveness when compared before and after the training period. CONCLUSION: A six week swimming training programme has a beneficial effect on aerobic capacity but not on histamine responsiveness in children with asthma.